Nanoemulsion from Piper aduncum, Cymbopogon nardus, and Bacillus thuringiensis to Control Xanthomonas axonopodis pv. allii - Ly Lan Phuong; Eka Candra Lina; Yulmira Yanti (International Journal of Agricultural Sciences, 2022)
The bacterial species Xanthomonas axonopodis pv allii (Xaa) is an important pathogen causing leaf blight in shallots. The use of botanical pesticides with nanoemulsion formulations has become a common alternative. This study aims to determine the characteristics and optimum concentration of the mixture of essential oil of Piper aduncum and fragrant Cymbopogon nardus waste. Nanoemulsion formulations are made using spontaneous emulsification methods. Besides, testing Bacillus thuringiensis strain MRSNR3.1 and its secondary metabolites toxicity against Xaa was carried out by the diffusion method using paper discs to determine the diameter of the inhibition zone. The results demonstrate that all four concentrations, 1%, 2.5%, 5%, and 7.5%, could control Xaa bacteria. A concentration of 1% is considered more optimal than the other three   concentrations in bactericidal effects against Xaa, as manifested in the formed clear zone (diameter of 3.17 cm). Besides, Bacillus thuringiensis strain MRSNR3.1 and its secondary metabolites were also effective againstXaa after four days of incubation with inhibition zones of 3.04 ± 0.44and 2.21 ± 0.28, respectively. Hence, it is concluded that nanoemulsion at 1% concentration and Bacillus thuringiensis strain MRSNR3.1 have  bactericidal properties that can be used to control Xaa